Creativity, geopolitics and ontological security: satire on Russia and the war in Ukraine. Issue 3 (3rd July 2017) - Edenborg, Emil
ABSTRACT: Some states create geographical imaginaries that envision the homeland as coherent and good, and the spaces of Others as disordered, dangerous and therefore legitimate objects of violence. Such 'violent cartographies' serve not only to justify policy actions, but constitute bordering practices aiming to provide stability, integrity and continuity to the Self, sometimes referred to as 'ontological security'. This article examines the role of creativity and artistic imagination in challenging dominant geopolitical narratives. It examines satire on the Russian-language internet, which played upon the Russian state's geopolitical narrative about the war in Ukraine 2014–15. Three themes within this dominant narrative – (1) the imperialist idea of Russia as a modernising force, (2) the gendering of Ukraine as feminine and Europe as homosexual and (3) the idea that the current war was a re-enactment of Russia's historical battle against fascism – all became the object of fun-making in satire. I argue that satire, by appropriating, repeating but slightly displacing official rhetoric in ways that make it appear ridiculous, may destabilise dominant narratives of ontological security and challenge their strive towards closure. Satire may expose the silences of dominant narratives and undermine the essentialism and binarism upon which they rely, opening up for estrangement and disidentification.